2008
DOI: 10.1111/j.1467-629x.2007.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and disclosures on the transition to International Financial Reporting Standards

Abstract: For reporting periods ending on or after 30 June 2004, Australian companies were required to disclose the expected impact of applying Australian equivalents of International Financial Reporting Standards effective from 1 January 2005. The objective of this paper is to examine the association between the level of disclosure and corporate governance quality. Using a sample of listed companies with 30 June balance dates, we find that the quantity of disclosure was positively related to some aspects of superior co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(199 citation statements)
references
References 53 publications
11
183
5
Order By: Relevance
“…This is in line with findings by Kent and Stewart (2008) which suggest a positive relationship between the number of board meetings and the level of disclosed information. The number of board and audit committee meetings appears to be a good proxy for the diligence and effort of the relevant board members (Lee et al, 2004), which has a positive impact on firms' CSR reporting.…”
Section: Discussionsupporting
confidence: 80%
“…This is in line with findings by Kent and Stewart (2008) which suggest a positive relationship between the number of board meetings and the level of disclosed information. The number of board and audit committee meetings appears to be a good proxy for the diligence and effort of the relevant board members (Lee et al, 2004), which has a positive impact on firms' CSR reporting.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, relative size is defined as the ratio between the transaction value and the acquirer's total assets (obtained from the consolidated financial statements) in the end of the reporting period. -Listing status (listing): Kent and Stewart (2008) argue that a better corporate governance structure leads to better disclosure levels and they obtained empirical evidence with Australian companies that confirm this relation. Murcia and Santos (2009) Murcia and Santos (2009) found that companies from the electric sector, subject to the standards of ANEEL, have higher disclosure level than the other companies.…”
Section: Control Variablesmentioning
confidence: 96%
“…While several studies argue that smaller boards are more advocate the convenience of larger boards as these could manage more effectively the complexity of today's business environments (Frías, Rodríguez, & García, 2013;Gandía, 2008;Kent & Stewart, 2008;Willekens, Bauwhede, Gaeremynck, & Gucht, 2005). This debate about effectiveness is also extended to the level of activity of BDs.…”
Section: Csr Disclosurementioning
confidence: 99%